The transitional justice framework agreed between the Colombian Government and the FARC-EP (2018)
This chapter analyses the transitional justice framework defined by the peace agreements between the Fuerzas Armadas Revolucionarias de Colombia—Ejercito del Pueblo (FARC—EP) and the Colombian Government. Peace talks began officially in November 2012, with the parties reaching an agreement on 24 September 2016. The agreement on the victims of the conflict starts with the recognition by the government and the FARC—EP that the main aim of this agreement is to compensate victims. When the FARC—EP entered into a negotiation process with the Colombian Government, they did not entertain the possibility of embracing a transitional justice framework. The agreement recognizes the clarification of truth, coexistence, and non-repetition as one of the mechanisms that victims' organizations have demanded, thus its inclusion not only responds to best practices in the field but also to the citizen's demands. The agreement explicitly addresses forced disappearances, given that it is one of the main crimes of the Colombian armed conflict.